2022
DOI: 10.29303/jppipa.v8i4.1669
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Student Learning Motivation through the Use of Interactive Digital Books Based on Project Based Learning (PjBL)

Abstract: This research aims to increase student learning motivation through the use of interactive digital books based on project based learning. Biology learning strategy and design is one of the compulsory subjects that must be taken by students of the biology education study program at the University of PGRI West Sumatra and STKIP Ahlussunnah Bukititinggi. Based on observations made in the class of 2020 students who are taking biology learning strategy and design courses at the Biology Education Study Program at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…(Gunawan et al, 2017). This is in line with research conducted by Susanti and friends (Susanti et al, 2022) shows that there is an increase in student learning motivation through the use In addition, it can also improve students' creative thinking skills and increase learning effectiveness to obtain high learning outcomes (Suradika et al, 2023;Yanti et al, 2023;Yufrizal, 2021). Other research conducted by Chan Lin (ChanLin, 2008) regarding the use of technology in project-based learning also showed that all students who participated in the project were able to achieve their project objectives as evidenced by their achievements related to the development of skills and abilities to synthesise and elaborate knowledge, their positive attitudes to participating in scientific exploration, and their willingness to use technology to conduct and report their research.…”
Section: Resultssupporting
confidence: 93%
“…(Gunawan et al, 2017). This is in line with research conducted by Susanti and friends (Susanti et al, 2022) shows that there is an increase in student learning motivation through the use In addition, it can also improve students' creative thinking skills and increase learning effectiveness to obtain high learning outcomes (Suradika et al, 2023;Yanti et al, 2023;Yufrizal, 2021). Other research conducted by Chan Lin (ChanLin, 2008) regarding the use of technology in project-based learning also showed that all students who participated in the project were able to achieve their project objectives as evidenced by their achievements related to the development of skills and abilities to synthesise and elaborate knowledge, their positive attitudes to participating in scientific exploration, and their willingness to use technology to conduct and report their research.…”
Section: Resultssupporting
confidence: 93%
“…To overcome this, the author made the following solutions: Taking a direct approach to students who are considered not confident in accessing digital learning media and in expressing opinions to provide motivation and guidance. This is in accordance with the study conducted by (Danin & Kamaludin, 2023;Fransiskus De Gomes, 2019;Susanti et al, 2022) states that Both in class and outside the classroom and outside active learning hours. Encouraging through group and classmates to provide assistance related to learning difficulties and to be more active in involving and giving them the opportunity to argue and ask questions.…”
Section: Supporting and Inhibiting Factorssupporting
confidence: 92%
“…Hasil ini sesuai dengan penelitian sebelumnya bahwa pembelajaran berbasis proyek mampu memberikan dampak positif terhadap motivasi mahasiswa (Chiang & Lee, 2016). Motivasi mahasiswa dapat ditingkatkan melalui proses pembelajaran berbasis proyek (Shin, 2018;Susanti et al, 2022). Gambar 3 menunjukkan hasil 85,2% mahasiswa sangat setuju dan 14,8% mahasiswa setuju bahwa materi Fermentasi yang menjadi topik dalam pembelajaran berhubungan dengan kehidupan sehari-hari.…”
Section: Hasil Dan Pembahasanunclassified